2022
DOI: 10.37934/arfmts.97.1.85104
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy as an Alternative Energy Source: Progress and Development to Meet the Energy Mix in Indonesia

Abstract: Government policies in Indonesia have been pushing in the past decade towards 100% electrification target by end of 2020. However, many of the new energy policies are reused from previous policies designed for different objectives causing overlap in policies between the central and local governments. Local distributed generation are not fully controlled by local stakeholders and community, and with the lack of long-term planning, continuous government incentives and support, they are bound to fail due to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Utilization of waste from the palm oil industry (such as empty fruit bunches, mesocarp fiber, and palm kernel shell) as a source of biomass energy is expected to be one of the efforts to increase the sustainability of palm-based bioenergy [262]. In addition, the use of non-edible parts of plants as a source of bioenergy can also reduce food and energy conflicts [267].…”
Section: Contribution Of the Forest Sector To Bioenergymentioning
confidence: 99%
“…Utilization of waste from the palm oil industry (such as empty fruit bunches, mesocarp fiber, and palm kernel shell) as a source of biomass energy is expected to be one of the efforts to increase the sustainability of palm-based bioenergy [262]. In addition, the use of non-edible parts of plants as a source of bioenergy can also reduce food and energy conflicts [267].…”
Section: Contribution Of the Forest Sector To Bioenergymentioning
confidence: 99%
“…The transition from conventional energy transformation methods to the use of renewable energies invites us to venture into new ways of generating energy through increasingly cleaner sources [1][2][3]. As is the use of biomass material, which, being a residue of agro-industrial processes, can be used for energy generation as indicated in previous studies [4,5]. What leads to studies to generate new forms of energy transformation, is how biomass presents in its composition a high potential in its volatile material, and its fewer polluting emissions are based on a fuel that will have a high content of H 2 and not based on hydrocarbon chains that increase the carbon footprint in its emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In countries such as Indonesia, rice husks are abundant, serving as readily available sources of biomass [3]. The widely used technique for converting solid materials, such as rice husks into gas fuel is gasification [4][5][6]. Research has extensively explored the use of rice husks and sawdust for energy production through gasification [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%